2008
DOI: 10.1161/circulationaha.107.720953
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Angina in Women Versus Men

Abstract: Background-In the absence of previous international comparisons, we sought to systematically evaluate, across time and participant age, the sex ratio in angina prevalence in countries that differ widely in the rate of mortality due to myocardial infarction. Methods and Results-We searched MEDLINE and EMBASE until February 2006 for healthy population studies published in any language that reported the prevalence of angina (Rose questionnaire) in women and men. We obtained myocardial infarction mortality rates f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
99
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(110 citation statements)
references
References 82 publications
6
99
0
5
Order By: Relevance
“…This result is consistent with other studies (33,34). Female patients usually show lower level of coping with illness compared to male patients and they use different coping mechanism (35). Other researchers reported that the complications of ACS are greater in female patients than in male patients (36).…”
Section: Discussionsupporting
confidence: 92%
“…This result is consistent with other studies (33,34). Female patients usually show lower level of coping with illness compared to male patients and they use different coping mechanism (35). Other researchers reported that the complications of ACS are greater in female patients than in male patients (36).…”
Section: Discussionsupporting
confidence: 92%
“…The higher prevalence of IHD in women than in men is similar to results from Hemingway et al 11 in a metaanalysis of 74 studies carried out in different countries. The authors found, through the use of random effect models, that the prevalence of IHD among females was consistently greater than among men, independent of age, the baseline year of the study, the birth cohort, ethnic origin and mortality rates.…”
Section: Referencessupporting
confidence: 87%
“…In Hemingway's meta-analysis 19 the prevalence of angina in populations under 45 years of age was even lower, namely between 3.2 and 3.8%.…”
Section: Discussionmentioning
confidence: 93%